Household Air Pollution Intervention Implications: Findings from Qualitative Studies and a Field Trial of Clean Cookstoves in Two Rural Villages in India - Alam, Ashraful (Int J Environ Res Public Health, 2016)
Exposure to household air pollution is estimated to be the 3rd largest contributor to the global burden of disease and the largest contributor in South Asia. Unacceptability of improved cook stoves by the intended user has been identified as a crucial factor hindering uptake and sustained use. We conducted a qualitative study to understand the socio-cultural factors that influence acceptance of improved cookstoves and conducted a systematic field trial in two rural villages in Maharashtra, India. The qualitative study used semi-structured in-depth interviews and focus group discussions. We included women primarily responsible for household cooking, their husbands, senior women in their households, and community health workers. We also conducted kitchen observations. The results indicated low awareness and knowledge of the health risks associated with traditional cookstove use although high prevalence of household air pollution (HAP) exposure symptoms among all groups. Women were resigned to using traditional cookstoves although they did not like them. The field trial findings were dominated by responses concerned with convenience and health advantages. We identify important issues to be considered when introducing an improved cookstove programme that will increase acceptability and potentially sustained used of improved cookstoves.